Polemistul Eugen Ionescu din « NU » si năzuinta lui spre centru - Cofan, Alunita (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
Our analytic research proposes an exegesis of young Eugene lonescu's polemic pages in his tome of critique published in Romanian in 1934. Our analytic perspective will consider the meaning of aesthetic values in literature and critique in order to impose a minoritary culture on a universal level. The critical nihilism in NO comes as a result of the pressure of the author's longing for the recognition of true cultural values; a pressure which cannot accept any compromise. Eugene Ionescu is a Robespierre of inter-war Romanian critique, who wanted, through a combative critique, to open a way for the Romanian culture towards the center of European culture. Abstract. Lair Samuel, Octave Mirbeau et les
The polemist Eugene Ionescu in "NO" and his longing for the center